2002
DOI: 10.1046/j.1365-2109.2002.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stocking density and feeding levels on growth and feed efficiency of Nile tilapia (Oreochromis niloticus L.) fry

Abstract: The effects of stocking density and feeding levels on larval survival, growth rates, feed utilization efficiency and body composition of Nile tilapia (Oreochromis niloticus L.) fry were investigated in two consecutive experiments. In experiment 1, swimup fry (0.016 g average body weight) were stocked in 20‐L fibreglass tanks, in a closed, recirculating indoor system, at five stocking densities (3, 5, 10, 15 and 20 fry L−1) and fed a larval test diet (40% crude protein) to apparent satiation, three times a day,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
89
1
16

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(139 citation statements)
references
References 10 publications
19
89
1
16
Order By: Relevance
“…On the other hand, fish farmed in highly populated ponds usually display lower growth rates (El-Sayed, 2002). The results of this study follow this trend, since the higher stocking biomass observed in pond 6 translated into lower slaughtering weight, despite higher productivity, compared with the less populated ponds 2, 3, 4, 5 and 9.…”
Section: Resultssupporting
confidence: 72%
“…On the other hand, fish farmed in highly populated ponds usually display lower growth rates (El-Sayed, 2002). The results of this study follow this trend, since the higher stocking biomass observed in pond 6 translated into lower slaughtering weight, despite higher productivity, compared with the less populated ponds 2, 3, 4, 5 and 9.…”
Section: Resultssupporting
confidence: 72%
“…The best feeding strategy for tambaqui during the first growth phase in cages was found to be 10% body weight/day (Silva and Gomes, 2007). The optimum stocking density and feeding level of Nile tilapia fry were reported to be 5 fry/L and 30% (crude protein) daily (El-Sayed, 2002). The optimum commercial stocking density, for survival, fast growth and high production rates of silver perch were examined by Rowland et al (2006).…”
Section: Feeding Strategymentioning
confidence: 99%
“…The type of feed and feeding frequency has a direct effect on water quality, growth, fish welfare and responses of the immune system (Riche et al, 2004;Silva et al, 2007;Garcia and Villarroel, 2009;Luthada and Jerling, 2013). Stocking density and ration size also influence growth, survival, and the innate immune system (El-Sayed, 2002;Rowland et al, 2006;Salas-Leiton et al, 2010). Farming factors may cause stress and disturb fish homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…As tilápias representam o segundo peixe de água doce mais criado no mundo, tanto em regiões tropicais quanto subtropicais e temperadas (El-Sayed, 2002;Borghetti et al, 2003) e, em razão de seu potencial, muitos aspectos relacionados ao manejo e à nutrição têm sido estudados (Furuya et al, 2001;Hayashi et al, 2002;Boscolo et al, 2002ab;El-Sayed, 2002;Meurer et al, 2003a). A fase inicial da criação é responsável pela produção de alevinos em quantidade e qualidade para o sucesso nas fases posteriores.…”
Section: Introductionunclassified